Synthesis and Characterization of Zn-Doped TiO2 Nanoparticles via Sonochemical Method - Wattanawikkam, C.; Pecharapa, W. (My University, 2015)
Zn-doped TiO2 nanoparticles were successfully fabricated using sonochemical method accompanying post calcination process. Titanium isopropoxide (Ti[OC3H7]4) and Zinc chloride (ZnCl2) were used as starting precursors for Ti and Zn sources, respectively. The homogeneous mixing solution of different Zn (0-1 mol%) and Ti ratio were irradiated in high intensity ultrasound sonometer (750 W 20 kHz) for 30 min at room temperature to obtain as-synthesized Zn-doped TiO2 nanoparticles followed by calcination at 400-700°C. To evaluate the structure and phase identification of prepared powders, the X-ray diffraction (XRD) and Raman spectroscopy were employed. The results reveal that the as-synthesized Zn-doped TiO2 nanoparticles are in anatase phase and their crystallinity increases with increasing calcined temperature. The morphology of as-synthesized powders was investigated by transmission electron microscope (TEM). The effect of Zn content and calcinations temperature on TiO2 properties was also discussed. © 2015
Keywords: Nanoparticles; Sonochemical; Zn-doped TiO2